2005
DOI: 10.1007/bf03395516
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Analysis of the Relationship Between Fluency and the Training and Maintenance of Complex Math Skills

Abstract: In 2 experiments, each involving different mathematical operations, we compared 2 training procedures for teaching component math skills in terms of their effects on the learning and long-term maintenance of composite skills. The dependent variables were learn units to composite task mastery and performance on the composite task 2 months later. The independent variables were instruction in math facts under (a) fluency and (b) mastery conditions . The experiments used a simultaneous treatment design in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…As noted previously, research has shown benefits for students who respond fluently on basic academic tasks, such as addition and subtraction problems (Singer-Dudek & Greer, 2005).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…As noted previously, research has shown benefits for students who respond fluently on basic academic tasks, such as addition and subtraction problems (Singer-Dudek & Greer, 2005).…”
mentioning
confidence: 72%
“…These findings are important because achieving accurate and fast responses via brief practice sessions promotes automaticity and other educational outcomes. Students who do not perform fluently on basic skills, such as math facts and sight words, frequently have difficulties with more complex skills (Carnine, 1989;Cates & Rhymer, 2003;Chiesa & Robertson, 2000;Singer-Dudek & Greer, 2005;Woodward, 2006). The gains in math fluency also appeared to be socially valid in that participants improved their math fluency more than non-participant peers.…”
Section: Conclusion and Guidelines For Best Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Fewer studies have looked specifically at the development of math fluency. Those studies found correlations between fast rate instruction and each of the benefits associated with fluency theory (Singer-Dudek and Greer 2005;Binder 1996;Ivarie 1986). However, those studies focused on reading related competencies, with relatively little regard to the development and maintenance of mathematical skills, but differences do exist in children's math abilities at a young age (Floyd et al 2003).…”
mentioning
confidence: 95%
“…Fluency effects have been examined in several demonstration studies; however, rarely in experimental investigations (Singer-Dudek and Greer 2005). Fewer studies have looked specifically at the development of math fluency.…”
mentioning
confidence: 98%